The sailboat island and the New Horizons trajectory - Winter, Silvia M. Giuliatti [UNESP]; Winter, Othon C. [UNESP]; Neto, Ernesto Vieira [UNESP]; Sfair, Rafael [UNESP] (Elsevier B.V., 2015)
In previous works we have studied the location of stable regions in the Pluto-Charon system. Among the findings, we discovered an island of stability, named sailboat island. One of the main goals of the New Horizons mission, launched in 2006, is to have a flyby close to the Pluto-Charon system in order to explore it. In the present work we analyze the relevance of the sailboat island for the New Horizons mission. Firstly, we identify the location and extent of these stable trajectories in the physical space around Pluto. They go beyond the trajectory of Charon in a way that Charon never crosses such trajectories. We verify that the nominal trajectory of the New Horizons spacecraft passes near the region of the sailboat island trajectories, reaching the closest distance at about 1650 km. Analyzing an alternative trajectory for the spacecraft, known as Deep Inner SHBOT, we found that it is not as safe as the nominal trajectory, because it crosses a region of highly inclined trajectories located at the sailboat island. We also estimate the density of particles from the sailboat island in the physical space around Pluto in comparison with the density of particles from a well-known stable region of near circular trajectories close to Pluto. Finally, we identified the location of the densest regions, which corresponds to the highest probable location of particles of the sailboat island. Such locations can be considered as spots for search and new detections of bodies by the New Horizons cameras along the flyby close to the Pluto-Charon system. (C) 2014 Elsevier Inc. All rights reserved.
Keywords: Celestial mechanics; Kuiper Belt; Pluto